Sex Differences in Problem Alcohol Use in High School as a Function of Recent Sexual Violence Victimization or Perpetration - Badour, Christal L. (J Fam Violence, 2019)
To investigate sex differences in associations between sexual violence victimization (SVV), sexual violence perpetration (SVP), and binge drinking and/or alcohol problems among high school students. While SVV has been linked to problem alcohol use among young women, little research has addressed the unique associations of SVV and SVP on alcohol use/problems within both sexes. A cross-sectional analysis of 16,992 high school students’ self-reports of past-year SVP and SVV was used where SVV/SVP was defined by three tactics (sexual coercion, drug/alcohol-facilitated or incapacitated sex, and physically forced sex). Alcohol measures included past-month binge drinking and past-year alcohol problems. Rates of SVV were twice as high in females (21.2% vs. 13.3%), and SVP rates were twice as high in males (10.9% vs. 5.2%). SVV and SVP were each associated with an increased rate of current binge drinking and problem alcohol use for both sexes, across increasing numbers of SV tactics and within each of three tactics. After controlling for demographic and other risk factors including SVP, drug/alcohol-facilitated or incapacitated SVV was more strongly linked to binge drinking and alcohol problems among females. SVP was more strongly linked to binge drinking and alcohol problems among males (adjusting for SVV and other covariates). No sex differences emerged in associations between coerced or physically forced SVV/SVP and alcohol-related outcomes. Both SVV and SVP are associated with an increased likelihood of binge drinking and alcohol problems for males and females. Important sex differences emerged when SV tactics are considered.